The Influence Of The Accounting Information System And Internal Control On Receivables At PT. Sucofindo Bengkulu Branch - Dwi Seprianty Marunduri; Iwin Arnova; Helmi Herawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Basically, trade receivables have become part of a company's business processes. However, the difference is the way each company manages its receivables. Managing receivables of course requires several driving factors so that activities are carried out well, including the Accounting Information System and Internal Control. As will be presented in this research, we will find out how much influence the Accounting Information System and Internal Control has on the management of receivables at PT. Sucofindo Bengkulu Branch. One of the things that be attention namely the age of the receivables, where the maturity of the receivables will have the potential for the receivables to become uncollectible receivables. The method used in this research is a quantitative descriptive method, where the researcher describes the symptoms that occur from the data obtained and analyzes it to get an idea of ​​how influential the Accounting Information System and Internal Control is on Receivables at PT. Sucofindo Bengkulu Branch